Incorporação de materiais vegetais associados à simulação da solarização e produtos comerciais na sobrevivência de macrophomina phaseolina, no crescimento do meloeiro e atributos do solo - Moura, Isadora Nayara Bandeira Medeiros de (2019)
The melon (Cucumis melo L.) is one of the most cultivated vegetables in the Northeast especially mainly to its adaptation to edaphoclimatic conditions. The diseases of the root system, caused by soil-dwelling pathogens, has been increasing the losses in this crop and causing abandonment of areas. The fungus Macrophomina phaseolina, which causes gray stem rot, is difficult to control, because it has a wide range of hosts and resistance structures, allowing its survival for long periods in the soil. Thus, the search for alternative methods is increasing and it reconciles several methods of management, which are efficient in the production of melon. The objective of this work was to evaluate the effect of the incorporation of plant materials (cabbage and cassava), associated to the simulation of soil solarization and commercial products use in M. phaseolina survival, melon growth and soil chemical attributes. Two identical experiments were carried out in a greenhouse (UFERSA-RN), the first in the period from March to May, and the second from June to August, 2018. The experiments were of the DIC type, with nine treatments and five replicates. The pots had a capacity of 5 L were filled with soil (CAMBISSOLO HÁPLICO) and commercial substratum, in the proportion of 1: 1, and received the incorporation of plant material (cabbage and cassava). The treatments were cabbage incorporation associated with solarization simulation (SSR), incorporation of manioc associated with solarization simulation (MSS), simulation of solarization and addition of IFT-18® product (SSI), simulation of solarization and addition of Soil set® product and Compost Aid® (SSSC), cabbage incorporation associated with simulation of solarization and IFT-18® product (RSSI), cabbage incorporation associated with solarization simulation and Soil set® and Compost Aid® product (RSSSC), incorporation of cassava associated with simulation of solarization and IFT-18® product (MSSI), incorporation of manioc associated to simulation of solarization and Soil set® and Compost Aid® (MSSSC), soil only (CONTROL). In both experiments, 2 bags of nylon tissue were buried at 10 cm from the depth of each vessel, with 10 g of M. phaseolina inoculum. The solarization simulation was performed during 20 days. After this period, the seedlings of melon (Goldex) with 10 days were transplanted. The fungus survival analysis were performed at the end of the experiments, at 50 days, plant growth at 10, 20 and 30 days after transplanting, and the chemical attributes of the soil at the implantation and at the end of the conduction of the experiments. In the treatments where plant materials (cassava and cabbage) were incorporated, fungus inactivation occurred and plant development was observed under greenhouse conditions. Simulation of soil solarization and use of commercial products without addition of plant material did not inactivate M. phaseolina under controlled conditions and provided lower plant development. There was an increase in available phosphorus content, total organic carbon and Mg and Na attributes in treatments where plant materials were incorporated. The most sensitive chemical attributes of the evaluated treatments were pH, Mg, Na, K, P, COT, SB, V. It is possible to relate the treatments with greater efficiency in the control of M. phaseolina to their similar edaphic characteristics